PERAN KEADILAN DALAM PENANGANAN PELANGGARAN HAM DI INDONESIA - Dyana Sukma; Vanny Permata Rinda; Fikria Humaimah; Andi Mustika Rosa; Diva Rahdatul Hasnah; Syukran Setiawan; Alwi Sihab; Yofi Lasimta Mansur; Hambali (STKIP Subang, 2025)
The enforcement of Human Rights (HAM) in Indonesia still faces various serious challenges, especially in resolving cases of gross human rights violations that often stall at the investigation and inquiry stage. This study aims to analyze the role of justice in the process of handling human rights violations in Indonesia and identify the main obstacles in its implementation. Using a qualitative approach through literature study, this study examines various secondary sources in the form of books, journals, laws and regulations, and official documents from related institutions. The results of the study show that although there is a legal basis such as Law Number 26 of 2000 and the existence of the National Human Rights Commission, its implementation is still hampered by limited authority, political intervention, and a weak legal culture. Law enforcement has not fully sided with victims and has not been able to present the expected substantive justice. Therefore, institutional reform and strengthening of the legal system are needed so that the principle of justice truly becomes the foundation in handling human rights violations in Indonesia.